Dorsal Root Ganglion Stimulation to Treat Focal Postsurgical and Diffuse Chronic Pain: A Case Report. Issue 5 (19th May 2022) - Akuamoah, Latrice A.; Tupper, Connor; Nagrani, Sohan; Chapman, Kenneth B.
Abstract : Dorsal root ganglion stimulation (DRG-S) is widely accepted for treating focal pain syndromes. We present the case of a 46-year-old woman with severe lumbar radiculopathy with an implanted spinal cord stimulator (SCS) that had lost efficacy. She developed an incisional hernia after undergoing a minimally invasive, extreme lateral interbody fusion and SCS explant. After herniorrhaphy, she presented with severe pain at the T10-T11 dermatomes, which we treated with DRG-S. One-year after lumbar fusion, her refractory lumbar and radicular pain returned, which we ultimately treated with bilateral T12+S1 DRG-S. DRG-S was thus used to successfully treat focal postsurgical and diffuse chronic pain.